Evaluating the efficacy of Balakoranda taila kati vasti and Kumburu etaadhi pinda sweda in the management of Katigraha (Lumbar spondylosis) - Sanjida, G.; Samarawickrama, A.G. (University of Colombo, 2025)
In today’s world, humans suffer from many lifestyle-related disorders due to the adoption of modern lifestyles. Katigraha (Lumber spondylosis) is one such disorder, which is described as Sthana vishesha vyadhi in which the lumbar vertebra is mainly affected. The cardinal symptoms of Katigraha are Ruk (pain), Stambha (stiffness), and Graha (restricted movements). The main vitiated Dosha in Katigraha is Vata. Among the various types of treatment modalities mentioned in texts for Katigrha, Kati vasti and Pinda sweda are especially of use for physicians. Therefore, this study was designed to evaluate the efficacy of Kati vasti with Balakoranda taila mentioned in Ayurveda pharmacopoeia and fermentation with Kumburu etaadhi pinda sweda (guthli of gothyl Calophyllum inophyllum - Domba ata mada, oil of Azadirachta indica - kohomba thel, ghee, oil of Madhuka indica – Mee thel, castor oil, Santalum album - sandalwood, guthil of Caesalpinia boundue Roxb - Kumburu ata mada, seeds of Gossypium herbaceum - Kapu ata, leaves of Curcuma longa, seeds of Mimusops elingi Linn - Muna mal ata and sesame oil) prescribed by traditional physicians. Thirty patients, 30 - 70 years of age with Kati graha were selected for this study. Patients were diagnosed mainly by cardinal symptoms and with X-ray findings. The selected patients were treated with Balakoranda taila kati vasti and Kumburu etaadhi pinda sweda for a period of one month. Among the Katigraha patients, male patients were predominantly seen between ages of 41 - 50 years. In X-rays, presence of osteophytes were found in 37%. After the treatment period, all the symptoms were statistically significantly reduced and the mean initial pain (3.05 + 0.29) was reduced to 0.98 + 0.15 at the end of the treatment (41% reduction) (p<0.0243). Mean initial stiffness (0.8 + 0.16) was reduced to 0.47 + 0.072 (49.85%) (p<0.0036) and mean initial restricted movements (1.47 + 0.23) was reduced to 0.72 + 0.063 (reduced by 71.48%) (p<0.0231). The present study provides insight into the use of external medicaments as better, effective medical measures for the treatment of Katigraha.
Keywords: Katigraha; Ruk; Stambha; Graha; Kati basti; Pinda sweda